Komunikasi Dakwah Habib Alwi Assegaf - Sania Nurhayati; Heri Isnaini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This article discusses the da'wah communication strategy implemented by Habib Alwi Assegaf, a preacher known for his polite, inclusive, and heartfelt approach. This research focuses on the analysis of the discourse of his lectures that integrate universal Islamic values with the local wisdom of the Indonesian people. The research method used is a qualitative approach, with descriptive analysis of data in the form of lecture transcripts, da'wah videos, and audience responses. The results of the study show that Habib Alwi Assegaf uses three main strategies in his da'wah communication. First, the use of simple but meaningful language, which allows audiences from various social and educational backgrounds to understand the message conveyed. Second, an emotional approach that emphasizes compassion, empathy, and appreciation for the audience, thus creating personal closeness. Third, strengthening local cultural values, such as the tradition of mutual cooperation and customs, which are combined with Islamic teachings. This approach is not only effective in conveying religious messages, but also in building social harmony in a diverse society. This research shows that da'wah is not only a means of conveying religious teachings, but also a tool to strengthen relationships between individuals in a multicultural society. Thus, this study is expected to contribute to the development of da'wah communication studies in Indonesia.